The dynamic interactions between cellular-molecular physiology and the environment - future directions in cellular-molecular evolutionary biology - Torday, John S. (Henry Stewart Talks, 2016)
Basis for predictive medicine, Utility in rational drug design & improving medical practices, Bioethics based on physiologic principles, A universal database for the natural sciences, The ideal human living environment
Updated at 2020/04/17